If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -10 = 8x + 11 Reorder the terms: -10 + 9x = 8x + 11 Reorder the terms: -10 + 9x = 11 + 8x Solving -10 + 9x = 11 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -10 + 9x + -8x = 11 + 8x + -8x Combine like terms: 9x + -8x = 1x -10 + 1x = 11 + 8x + -8x Combine like terms: 8x + -8x = 0 -10 + 1x = 11 + 0 -10 + 1x = 11 Add '10' to each side of the equation. -10 + 10 + 1x = 11 + 10 Combine like terms: -10 + 10 = 0 0 + 1x = 11 + 10 1x = 11 + 10 Combine like terms: 11 + 10 = 21 1x = 21 Divide each side by '1'. x = 21 Simplifying x = 21
| ab-4a+3ab+2a= | | 300x-100=-40+50x | | 13a+56=4a+119 | | 12x+8-5=75 | | 3p=5p | | 14(v+3)-2v=4(3v+3)-18 | | 10a+33=2a+81 | | 11x-16=5(2x+4)-4 | | 3x-7=-7x-37 | | 6e+2y-4e-7y= | | 20-9k=-7k+66 | | x-sqrtx-6=0 | | 0.16y+0.04(y+9000)=1560 | | -8b=-12 | | 9x+4Y-36=0 | | y-5=7-17 | | 14a-9=5a-63 | | 2b-5-10b-7= | | 7x+2y+9z-4x+5z-4y= | | 6a+14=4a+28 | | -3(z+9)= | | 10-6(8x-2)9x-(3+4x)= | | x=31 | | 5x-35y=20 | | 8z+4z= | | 12d+20de= | | 5x+2(x-4)=5x+x-10 | | (3-8i)(7+i)= | | 2w^2+8w=-7w^2-3w+14 | | 6y^2-20y+16=0 | | 4c+16=3c-6 | | -4x+5y-7= |